If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y+6=3y-9
We move all terms to the left:
y+6-(3y-9)=0
We get rid of parentheses
y-3y+9+6=0
We add all the numbers together, and all the variables
-2y+15=0
We move all terms containing y to the left, all other terms to the right
-2y=-15
y=-15/-2
y=7+1/2
| 2(1x-6)+6=4x-2 | | 17=3q+2 | | 7j+2=40 | | u2-4u-21=0 | | -15=-25+8x | | b=-2+2/5+1/5 | | 4x÷3=2x-4 | | .5(5x+1)=3 | | v2-10v+21=0 | | 4/r+2=5 | | 3x+7×=52 | | (5u+5)/6+(5u+10)/9=5 | | 10(y+4)=5(3y-) | | 1/4+4c=5/4 | | -12/p=12 | | -1/5*b-2/5=-2 | | 3x+15-5x=-25+6x | | 5/4=4c+1/2 | | u−14–4=–1 | | -1/2(b-6)=5. | | m3+ 5=7 | | 9y-6=4y+15 | | −x+6=8 | | 2x+3+3x=x+11 | | 3x+45-5x=-25+6x | | -4x-3x-40=-3(2x-20) | | 44=10+x | | nn^2=225 | | 3(5x+4)=13x-4 | | “n”n^2=225 | | -27=5y+13 | | -4/9(-9/4)=x/108(-9/4) |